ARCHITECTURAL COMPONENT IN THE TEXTBOOK “ART” (THE EXPERT ASSESSMENT METHOD) - Nychkalo, Svitlana (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article is devoted to use the expert assessment method of the architectural component of the textbook “Art” (by O.A. Komarovska et al.). It is emphasized on the importance of the art of architecture in the aesthetic education of schoolchildren, which is carried out primarily at art lessons. This requires appropriate scientific and methodological materials, including textbooks. Problems of their quality are of great scientific and practical interest. To solve these problems, there is a need of teachers’ feedback who use textbooks in their work. The expert assessment method provides the opportunity for effective testing of the textbook. According to the purpose of the study, based on the analysis of scientific sources, the expert assessment method of the art of architecture was determined. The questionnaire for experts has been developed, which reflects the criteria of aesthetic education and the tasks set by the authors of the textbook. The article describes the course of the survey, outlines its indicators. As a result, it was revealed which features of the presentation of educational material in the textbook received more support from experts, and vice versa. The examples of expert comments that can be considered as a methodological basis for improving the writing of similar textbooks in the future are given. The attention is drawn to certain contradictions, such as between the scientific style of presentation of the material, the excessive amount of information in some textbooks and the possibility of their perception by students. The results of the study confirmed the feasibility of expert assessment of educational and methodological literature. The obtained indicators showed teachers and scholars’ positive attitude towards the presentation of the art of architecture in this textbook. According to their assessments and wishes, the ways of improvement and diversification of methods of aesthetic education of schoolchildren are determined.